Penerapan Model Problem Based Learning Berbantuan Media Lentera Untuk Meningkatkan Pemahaman Konsep IPAS Siswa Kelas IV - Ellayati Rafsanjani; Lovika Ardana Riswari; Rihayati Rihayati (TA'DIBAN, 2025)
This study aims to improve students’ conceptual understanding of IPAS in the topic "Aku dan Kebutuhanku" through the implementation of the Problem Based Learning (PBL) model supported by LENTERA (Interactive Cabinet) media. The research was conducted as a two-cycle Classroom Action Research (CAR) in the fourth-grade class of SD 4 Bulungcangkring, involving 40 students. The results showed a significant increase in active participation and conceptual understanding after the implementation of the PBL method and LENTERA media. The average level of student understanding increased from 56% in the pre-cycle to 62.5% in the first cycle, and 82% in the second cycle, indicating a 26% improvement. The conclusion of this study is that the implementation of the PBL model supported by concrete and interactive media is highly beneficial and has proven to be effective in enhancing students’ active engagement and improving their understanding of IPAS content.